Optimalisasi Desain Mesin Perajang Keripik Pisang Mempertimbangkan Nilai Ergonomi - Nila Nurlina; Ahmad Dony Mutiara; Mujahid Wahyu (Jurnal Teknik, 2021)
Micro, small and medium enterprises have an important role in supporting the national economy. They need to be supported to be able to compete globally. This study aims to design a banana chip slicer machine by considering the ergonomics of the research partners. The object of the research is the process of banana slicing done by a banana chips maker located in Kediri Regency, East Java Province. The Business actors have been running their business since 2010 with 10 employees. Slicing is one of the key processes which determines the product quality in the manufacturing of banana chips. The problem that occurs in the object of observation is that the chopping is done manually, carried out with the same movements, and repeatedly, takes a long time to cause musculoskeletal disorders, namely impaired function of the muscles, joints, and spine. The problem that occurs in the object of observation is that the slicing was done manually for a long time, carried out with the same repeated movements, causing cause musculoskeletal disorders, namely impaired function of the muscles, joints, and spine. In addition, workers must be trained and precise in slicing bananas to get the same thickness. Slicing is done on a wood-fueled pawon stove which interferes with breathing. Furthermore, the slicing movements must be carried out as quickly as possible which can result in injury to the hands and their muscles. In the current condition, the research results showed a high RULA value, namely 6. Optimization was successfully carried out with two schemes. The first scheme used a slicing machine design using arm support and repetitive motion. While the second scheme used a slicing machine design with arm support and intermittent movement. The simulation of the two schemes showed a decrease in RULA value from 6 to 2, which means the process is acceptable and safe for workers.